Effects of a Mindfulness-Based Intervention on Self-Compassion and Psychological Health Among Young Adults With a History of Childhood Maltreatment - Joss, Diane; Khan, Alaptagin; Lazar, Sara W.; Teicher, Martin H. (Frontiers in Psychology, 2019)
Individuals who were maltreated during childhood are faced with increased risks for developing various psychological symptoms that are particularly resistant to traditional treatments. This pilot study investigated the effects of a mindfulness based behavioral intervention for young adults with childhood maltreatment history. This study looked at self-report psychological questionnaires from 20 subjects (5 males) before and after a mindfulness-based behavioral intervention, compared to 18 subjects (6 males) in the waiting list control group (age range 22-29); all subjects experienced mild-to-moderate childhood maltreatment. Our results showed that the mindfulness group had reduced stress (t(18) =-3.529, p = 0.002, d =0.809) and anxiety (t(19) = -2.945, p = 0.008, d = 0.659), as well as increased mindfulness (t(17) = 2.265, p = 0.037, d = 0.534) and self-compassion (t(15) = 4.505, p < 0.001, d = 1.126). No significant changes were observed in the waiting list control group. Linear mixed effects model analyses revealed significant group by time interaction on stress (F(1,36)=9.486, p = 0.004), anxiety (F(1,36) = 7.079, p = 0.012), and self-compassion (F(1,32) =11.159, p = 0.002). Partial correlation analyses showed that after controlling for group identity and childhood maltreatment severity, changes in mindfulness positively correlated with changes in self-compassion (r = 0.578, p = 0.001, df = 26), which negatively correlated with changes in depression (r = -0.374, p = 0.05, df = 27) and anxiety (r = -0.395, p = 0.034, df = 27). Changes in self-compassion mediated, in part, the relationship between changes in mindfulness and changes in anxiety (average causal mediation effect = -4.721, p = 0.014). We observed a dose-dependent effect of the treatment, i.e., the number of intervention sessions attended were negatively correlated with changes in stress (r = -0.674, p = 0.002, df = 16), anxiety (r = -0.580, p = 0.009, df = 17), and depression (r = -0.544, p = 0.020, df = 16), after controlling for the individual differences in childhood maltreatment severity. Our results suggest that, to some extent, the mindfulness-based intervention can be helpful for improving self-compassion and psychological health among young adults with a childhood maltreatment history.